2012
DOI: 10.1111/j.1365-2125.2011.04130.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between BclI polymorphism in the NR3C1 gene and in vitro individual variations in lymphocyte responses to methylprednisolone

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • In vitro lymphocyte steroid sensitivity has been suggested as a useful tool to predict in vivo response to glucocorticoid treatment in different inflammatory chronic diseases. • A correlation between genetic polymorphisms and clinical response to glucocorticoids has been demonstrated in these patients. WHAT THIS STUDY ADDS • The BclI polymorphism in the glucocorticoid receptor (NR3C1) gene is associated with higher methylprednisolone potency in vitro. • The combined e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
(22 reference statements)
1
23
0
2
Order By: Relevance
“…In a small study, the frequency of the G allele was found to be significantly higher in the asthmatic population compared to controls (25). Even more relevant to our results is the observation that G allele was associated with hypersensitivity to glucocorticoids (26)(27)(28). Hence, it can be speculated that the increased sensitivity associated with the G allele of the rs41423247 may account for the better response of the asthmatic children carrying this allele.…”
Section: Discussionsupporting
confidence: 53%
“…In a small study, the frequency of the G allele was found to be significantly higher in the asthmatic population compared to controls (25). Even more relevant to our results is the observation that G allele was associated with hypersensitivity to glucocorticoids (26)(27)(28). Hence, it can be speculated that the increased sensitivity associated with the G allele of the rs41423247 may account for the better response of the asthmatic children carrying this allele.…”
Section: Discussionsupporting
confidence: 53%
“…In a large group of Dutch elderly individuals, subjects with the G allele had lower cortisol levels after dexamethasone suppression test as well as a tendency towards a decreased lean body mass and abdominal fat distribution, high blood pressure, altered insulin sensitivity, and cardiovascular risk factors, suggesting hypersensitivity to GC (38). In 42 blood donors, association between the BclI variant genotype and an increased in vitro sensitivity to GCs was observed by DEX-mediated inhibition of concanavalin-A-stimulated PMBC (40). On the contrary, our data show no differences in BMI, Kd, IC 50 , and early morning serum or salivary cortisol concentrations at baseline and after dexamethasone suppression tests among BclI genotype groups.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, within-individual variation in lymphocyte sensitivity, expressed as maximum inhibition achieved (Imax), is low, and the degree of resistance in a given individual remains relatively constant over time, at least for healthy subjects [25]. In addition, a recent study [13] has shown an association between the BclI mutated genotype, in the GR gene, previously associated with a better response to glucocorticoids in pediatric patients with inflammatory bowel disease [17,26], and an increased in vitro sensitivity to glucocorticoids in healthy subjects. Of particular interest are the observations that the results of this pharmacodynamic in vitro test can be correlated with the clinical response to glucocorticoids in different diseases such as rheumatoid arthritis [27,28], systemic lupus erythematosus [29], bronchial asthma [30][31][32][33], renal transplant rejection [34] and ulcerative colitis [12,35].…”
Section: Pharmacodynamic Assays For Glucocorticoid Responsementioning
confidence: 98%
“…For pediatric inflammatory and autoimmune disease, the issue may be the collection of a tissue representative of the disease condition and suitable for a pharmacodynamic assessment. However, there are reports that primary cultures of peripheral leukocytes may be suitable for these assays, even in pediatric inflammatory diseases [12,13].…”
Section: Pharmacodynamic Assaysmentioning
confidence: 99%